La conjoncture économique canadienne : que nous réserve 1987 ? - Fortin, Franceline (Assurances, 1987)
The economic outlook for 1987 is, to some extent, a continuity of 1986: moderate growth, high unemployment and very volatile financial markets. To better understand the 1987 forecast, the author presents a brief retrospective of the economic and financial highlights of 1986. In general, the Canadian economy is expected to continue growing at a moderate rate of 3 %. Yields on financial markets should remain interesting although, given the highly volatile markets, these yields will not be any easier to earn than in 1986.